Effect of foliar Nitrogen and Sulphur spraying on white wine composition ( Vitis vinifera L.cv. Chenin Blanc and Sauvignon Blanc) - Bruwer, Freda Aléta (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.